Impact of Adjuvant Therapy Type on Survival in Stage II/III Rectal Cancer Without Preoperative Chemoradiation: A Korean Multicenter Retrospective Study - Kang, Byung Mo; Baek, Jeong-Heum; Park, Sun Jin; Baek, Seong Kyu; Park, Ki-Jae; Choi, Hong-Jo; Bae, Byung-Noe; Choi, Sun Keun; Kim, Kap Tae; Kim, Jin-Su; Lee, Suk-Hwan (Annals of coloproctology, 2018)
This study compared the oncologic impact of postoperative chemotherapy and chemoradiotherapy on patients with rectal cancer without preoperative chemoradiation. This retrospective study analyzed 713 patients with a mean follow-up of 58 months who had undergone radical resection for stage II/III rectal cancer without preoperative treatment in nine hospitals from January 2004 to December 2009. The study population was categorized a chemotherapy group (CG, n = 460) and a chemoradiotherapy group (CRG, n = 253). Five-year overall survival (OS) and disease-free survival (DFS) were analyzed, and independent factors predicting survival were identified. The patients in the CRG were significantly younger (P < 0.001) and had greater incidences of low rectal cancer (P < 0.001) and stage III disease (P < 0.001). Five-year OS (P = 0.024) and DFS (P = 0.012) were significantly higher in the CG for stage II disease; however, they were not significantly different for stage III disease. In the multivariate analysis, independent predictive factors were male sex, low rectal cancer and stage III disease for OS and male sex, abdominoperineal resection, stage III disease and tumor-positive circumferential margin for DFS. However, adjuvant therapy type did not independently affect OS (hazard ratio [HR], 1.243; 95% confidence interval [CI], 0.794-1.945; P = 0.341) and DFS (HR, 1.091; 95% CI, 0.810-1.470; P = 0.566). Adjuvant therapy type did not affect survival of stage II/III rectal cancer patients without neoadjuvant chemoradiotherapy. These results suggest that adjuvant therapy can be chosen based on the patient's condition and the policies of the surgeons and hospital facilities.